Out of the dark: transitional subsurface-to-surface microbial diversity in a terrestrial serpentinizing seep (Manleluag, Pangasinan, the Philippines) - Woycheese, Kristin M.; Meyer-Dombard, D'Arcy R.; Cardace, Dawn; Argayosa, Anacleto M.; Arcilla, Carlo A. (Frontiers in Microbiology, 2015)
In the Zambales ophiolite range terrestrial serpentinizing fluid seeps host diverse microbial assemblages. The fluids fall within the profile of Ca2+-OH–type waters, indicative of active serpentinization, and are low in dissolved inorganic carbon (<0.5 ppm). Influx of atmospheric carbon dioxide affects the solubility of calcium carbonate as distance from the source increases, triggering the formation of meter-scale travertine terraces. Samples were collected at the source and along the outflow channel to determine subsurface microbial community response to surface exposure. DNA was extracted and submitted for high-throughput 16S rRNA gene sequencing on the Illumina MiSeq platform. Taxonomic assignment of the sequence data indicates that 8.1% of the total sequence reads at the source of the seep affiliate with the genus Methanobacterium. Other major classes detected at the source include anaerobic taxa such as Bacteroidetes (40.7% of total sequence reads) and Firmicutes (19.1% of total reads). Hydrogenophaga spp. increase in relative abundance as redox potential increases. At the carbonate terrace, 45% of sequence reads affiliate with Meiothermus spp. Taxonomic observations and geochemical data suggest that several putative metabolisms may be favorable, including hydrogen oxidation, H2-associated sulfur cycling, methanogenesis, methanotrophy, nitrogen fixation, ammonia oxidation, denitrification, nitrate respiration, methylotrophy, carbon monoxide respiration, and ferrous iron oxidation, based on capabilities of nearest known neighbors. Scanning electron microscopy and energy dispersive X-ray spectroscopy suggest that microbial activity produces chemical and physical traces in the precipitated carbonates forming downstream of the seep’s source. These data provide context for future serpentinizing seep ecosystem studies, particularly with regards to tropical biomes.